1983
DOI: 10.1046/j.1537-2995.1983.23483276878.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus alloimmunization following intensive plasma exchange

Abstract: A 17-year-old woman was admitted to the hospital for the treatment of rapidly progressive systemic lupus erythematosus. She failed to improve when treatment with cyclophosphamide and prednisone and, therefore, was treated with intensive plasma exchange. A total of 24 liters of plasma was exchanged during six separate procedures over an 8-day period. The patient, who was blood group B Rh negative (Cde/cde), was found to have an IgG anti-D antibody reacting at a titer of 16 by the indirect antiglobulin technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There is also evidence that as few as 0.24 × 10 5 RBC of rhesus‐positive donors are sufficient for anti‐D‐production in rhesus‐negative recipients (4). Primary Rh alloimmunization can occur after transfusion of low numbers of RBC, as well as after plasma exchange (31, 33). Therefore, the use of plasma products with the lowest possible content of residual cells is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that as few as 0.24 × 10 5 RBC of rhesus‐positive donors are sufficient for anti‐D‐production in rhesus‐negative recipients (4). Primary Rh alloimmunization can occur after transfusion of low numbers of RBC, as well as after plasma exchange (31, 33). Therefore, the use of plasma products with the lowest possible content of residual cells is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that primary immunization will not take place following immunization with these low levels of RBCs. A case report, where one patient underwent plasma exchange with 24 L of plasma, showed that approximately 10 10 RBCs were able to induce primary D immunization 20 . Another case report indicates that transfusion of 12 D+ plasma units to a multiparous woman was able to elicit a secondary D response 21 .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that the minimum dose of RBCs necessary for primary immunization to D is only 0.03 mL, equivalent to approximately 0.24 × 10 9 RBCs 10 . Thus, primary Rh alloimmunization can occur after the transfusion of small quantities of RBCs, as after plasma exchange 11,12 . Boostering effects can be observed after the transfusion of as little as 4 units of FFP 13 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, primary Rh alloimmunization can occur after the transfusion of small quantities of RBCs, as after plasma exchange. 11,12 Boostering effects can be observed after the transfusion of as little as 4 units of FFP. 13 Hence, RBC alloimmunization may be significant when large volumes of plasma are used, especially in girls and women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%